2020
DOI: 10.1039/d0cc01849j
|View full text |Cite
|
Sign up to set email alerts
|

Unusually large fluorescence quantum yield for a near-infrared emitting DNA-stabilized silver nanocluster

Abstract: Silver nanoclusters stabilized by 5′-CCCGGAGAAG-3′ DNA strands display an unusually high fluorescence quantum yield in the near-infrared region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(100 citation statements)
references
References 31 publications
3
97
0
Order By: Relevance
“…28 The high steady-state anisotropy values are in line with previously reported time-resolved anisotropy values that are close to 0.4 at time zero. 10,11,29 Except for the 470 nm transition of the DNA811-AgNC, the other higher energy transitions in DNA841-AgNC and DNA811-AgNC are not aligned with the orientation of the 640 nm transition. Interestingly, for the 470 nm transition of the DNA811-AgNC, a similar excitation anisotropy close to 0.4 is found on the rededge of the transition, while the blue edge has an anisotropy value that drops gradually.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…28 The high steady-state anisotropy values are in line with previously reported time-resolved anisotropy values that are close to 0.4 at time zero. 10,11,29 Except for the 470 nm transition of the DNA811-AgNC, the other higher energy transitions in DNA841-AgNC and DNA811-AgNC are not aligned with the orientation of the 640 nm transition. Interestingly, for the 470 nm transition of the DNA811-AgNC, a similar excitation anisotropy close to 0.4 is found on the rededge of the transition, while the blue edge has an anisotropy value that drops gradually.…”
Section: Resultsmentioning
confidence: 97%
“…We have previously shown that the multiexponential nature of DNA-AgNCs can be explained by slow spectral relaxation (relaxation on the time scale of the excited state decay time). [8][9][10] Given the limited sensitivity of the Fluo-time300 detector above 800 nm, we opted to measure timeresolved emission spectra (TRES) only at À196 1C. The results can be found in Fig.…”
Section: Time-resolved Properties Of Dna841-agnc and Dna811-agncmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] This devoted attention is due to the peculiar luminescent properties of some DNA-AgNCs such as high fluorescence quantum efficiencies, resistance to photobleaching and wide wavelength tunability. [6,7,[9][10][11] These DNA-AgNCs consist of few silver atoms and cations (up to 30) enclosed in DNA strands, and their luminescence properties are related to the composition, charge and conformation of the AgNC. [6] In the last decade, DNA-AgNCs have emerged in a wide number of bioanalytical and biomedical applications, in particular as probes for the detection of specific analyte molecules, [12,13] since their bright, well-defined luminescence [14] and biocompatibility provides DNA-AgNCs with potential advantageous properties, compared to more traditional chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescent DNA‐stabilized silver nanoclusters (DNA‐AgNCs) have in recent years attracted significant interest [1–8] . This devoted attention is due to the peculiar luminescent properties of some DNA‐AgNCs such as high fluorescence quantum efficiencies, resistance to photobleaching and wide wavelength tunability [6,7,9–11] . These DNA‐AgNCs consist of few silver atoms and cations (up to 30) enclosed in DNA strands, and their luminescence properties are related to the composition, charge and conformation of the AgNC [6] .…”
Section: Introductionmentioning
confidence: 99%